Factors associated with the non-compliance of the child vaccination of diphtheria, pertussis and tetanus in Peru, year 2019: Factores asociados al incumplimiento de la vacunación infantil de difteria, pertussis y tétanos en Perú, año 2019 - Aquino-Sosa, Bryan A. (2022)
Introduction:Pertussis tetanus and diphtheria, (DPT) are highly contagious diseases in children; worldwide vaccination schemes have been established for the prevention of these pathologies. However, different factors can lead to non-compliance with them. Objective: To determine the factors associated with non-compliance with the vaccination schedule against diphtheria,pertussis and tetanus(DPT) in Peru in2019. Methods:Analytical, retrospective study of secondary source based on data from 7 187 mothers between 15 and 49 years old regarding the vaccination schedule of their children older than six months of age obtained in the Demographic and Family Health Survey (ENDES) Peru 2019.The vaccination schedule of children over six months of age and the sociodemographic variables of the mothers were analyzed. A bivariate and multivariate analysis was performed using the chi square test for independence (p<0,050). Results:The sample included in the study was 7 187 mothers surveyed regarding the vaccination schedule for their children older than six months of age. The variables associated with the incomplete scheme by multivariate analysis were: low educational level (RPa: 1,19; 95% CI: 1,02-1,40), not having health insurance (RPa: 1,41; 95% CI: 1,23-1,60), wealth index poor (RPa:1,19; CI95%: 1,02-1,40), age of the mother under 20 years (PR:2,63; CI95%:2,06-3,35) and having two or more children (PRa:1,36; CI95%:1,19 -1,57). Conclusion: The index factors of wealth, mother's age, low educational level, not having health insurance and having more than two children are associated with non-compliance with the DPT vaccination schedule.